The Roles of melanocortin 1 and 5 receptors in cardiac remodelling and their potential as therapeutic targets - Hallanheimo, Anni (fi=Turun yliopisto|en=University of Turku|, 2025)
Cardiac hypertrophy and heart failure are severe and progressive conditions with a poor prognosis and limited treatment options, and their morbidity and mortality rates remain high. The melanocortin system consists of melanocortin peptides and their receptors. Melanocortin peptides, including α-, β-, and γ-melanocyte-stimulating hormones (MSH), mediate their biological actions via five melanocortin receptors named from MC1R to MC5R. They are involved in multiple physiological functions, with MC1R particularly being recognised as the key regulator of skin pigmentation and MC5R in regulating exocrine gland activity. Melanocortins and their receptors have also established roles in the control of inflammation and vascular function, and the central regulation of energy homeostasis and cardiovascular function, but their local role in the heart has remained elusive. Consequently, the main objective of this thesis was to characterise the role of the melanocortin system in cardiac remodelling and to investigate pharmacological targeting of MCRs as a potential treatment for cardiac hypertrophy and heart failure. First, it was identified that α-MSH, MC1R, and MC5R are expressed in cultured cardiomyocytes and in the mouse heart. Experimental models of pathological cardiac hypertrophy demonstrated declining levels of α-MSH, as well as MC1R and MC5R, in the failing heart. Pharmacological treatment of mice with α-MSH protected against pathological hypertrophy and heart failure. Pharmacological activation of MC1R in cellular models promoted cardiomyocyte hypertrophy, while global and cardiomyocyte-specific MC1R deficiency reduced pathological and physiological cardiac hypertrophy in mice, but led simultaneously to left ventricular dilatation and compromised left ventricular function. Conversely, pharmacological activation of MC5R attenuated hypertrophic and fibrotic responses in experimental cell and animal models, while genetic MC5R deficiency aggravated pathological hypertrophy, fibrosis, and systolic performance in mice. In conclusion, this thesis identifies that the local melanocortin system exists in the heart and highlights novel roles for MC1R and MC5R in cardiac remodelling. These results suggest that MC1R and MC5R are promising therapeutic targets for the treatment of pathological cardiac hypertrophy and heart failure.

Melanokortiini 1 ja 5 reseptoreiden merkitys sydämen uudismuovautumisessa ja mahdollisuudet lääkekehityskohteina Sydämen liikakasvu ja vajaatoiminta ovat vakavia ja eteneviä oireyhtymiä, joilla on huono ennuste ja rajalliset hoitomahdollisuudet, ja joiden yleisyys ja kuolleisuus on edelleen korkea. Melanokortiinit ovat peptidejä, joihin lukeutuvat α-, β- ja γ- melanosyyttejä stimuloivat hormonit (MSH). Ne vaikuttavat moniin eri elimistön toimintoihin sitoutumalla melanokortiinireseptoreihin (MC1R - MC5R). MC1R säätelee erityisesti ihon väritystä ja MC5R umpieritysrauhasten toimintaa. Melanokortiinijärjestelmä osallistuu lisäksi merkittävällä tavalla elimistön tulehdusvasteisiin, verisuonten toimintaan sekä energiatasapainon ja sydän- ja verenkiertoelimistön keskushermostoperäiseen säätelyyn, mutta sen paikallista vaikutusta sydämessä ei tunneta. Tämän väitöskirjan keskeisimpänä tavoitteena olikin selvittää melanokortiinijärjestelmän merkitystä sydämessä ja arvioida sen mahdollisuuksia sydämen liikakasvun ja vajaatoiminnan hoidossa. Tämän väitöskirjatyön tutkimuksissa havaittiin, että α-MSH, MC1R ja MC5R ilmentyvät viljellyissä sydänlihassoluissa ja sydänkudoksessa. Kokeelliset sydämen liikakasvun mallit osoittivat α-MSH:n, MC1R:n ja MC5R:n määrien sydämessä laskevan vajaatoiminnan seurauksena. α-MSH hoito ehkäisi sairauteen liittyvää sydämen liikakasvua ja paransi sydämen supistusvaiheen toimintaa kokeellisessa tautimallissa. MC1R:n lääkinnällinen aktivointi edisti sydänlihassolujen kasvua, kun taas reseptorin puute hillitsi hiirillä sekä sairauteen liittyvää että liikunnan seurauksena kehittyvää sydämen liikakasvua aiheuttaen kuitenkin samanaikaisesti vasemman kammion laajentumista ja toiminnan heikkenemistä. MC5R:n aktivointi sekä kokeellisilla solu- että eläinmalleilla sitä vastoin vaimensi sydämen liikakasvua ja sidekudoksen muodostumista, ja reseptorin puute pahensi liikakasvua, lisäsi sidekudoksen muodostumista ja heikensi sydämen supistusvaiheen toimintaa hiirillä. Väitöskirjan löydökset osoittavat aktiivisen melanokortiinijärjestelmän löytyvän sydämestä ja todistavat sen merkityksen sydämen kasvun ja toiminnan säätelyssä, laajentaen ymmärrystä melanokortiinijärjestelmän vaikutuksista elimistössä. Lisäksi tulokset tukevat melanokortiineja vastaavien lääkeaineiden kehitystä sekä MC1R:n ja MC5R:n mahdollisuuksia toimia uusina lääkekehityskohteina sydän- ja verisuonisairauksien hoitoon.